Aufschwung vorbei: Zinsen belasten Wohnungsbau schwer - Tobias Just (Wirtschaftsdienst, 2023)
– In 2021, 293,000 dwellings were completed in Germany. This is at least 130,000 more than were completed at the low point in 2010, but less than the government had planned in order to limit the housing shortage. It is very likely, that residential construction is going to decline following the strong increase in interest rates and already falling residential prices. This decline in residential construction can only be expected in the short term; in the medium term there are good reasons to believe that Germany has not fi nished building. It is therefore important to ensure that the elasticity of construction supply is not reduced during this adjustment phase.
Keywords: E22; R31; R38; 330; Wohnungspolitik; Wohnungsbau; Deutschland